The effect of manual removal on movement distances in populations of signal crayfish (Pacifastacus leniusculus) - Moorhouse, T; Macdonald, D (Wiley, 2011)
1. Crayfish are amongst the most frequently introduced non-native aquatic organisms, with well-documented negative effects on a large number of freshwater taxa. Many crayfish-control strategies make use of manual removal by trapping, a method known preferentially to remove the largest individuals, leaving the juvenile population almost entirely untrapped. 2. Removal by trapping may be used in an attempt to delay colonisation of new stretches by invasive crayfish. It is, however, unclear what effects trapping may have on movement distances of crayfish in wild populations. We examine the impacts of removal by trapping on the movements of American signal crayfish in two UK rivers. 3. We studied four 100m stretches of two rivers, the Evenlode and Thame, comprising two removal and two non-removal stretches. Each river supported both treatments. Half of the crayfish captured from the removal sections were removed and humanely destroyed by freezing, and half were marked with their trap location and released there. All crayfish captured from the non-removal sections were marked and returned at the point of capture. 4. Mean movement distances were smaller in the removal stretches than the non-removal stretches, both within capture sessions (10.8 m and 16.0m, respectively) and between sessions (14.5 m and 24.6 m, respectively), suggesting that removal trapping resulted in the remaining crayfish making smaller movements. Crayfish with larger carapace lengths under both treatments made substantially larger movements than those with smaller carapace lengths, both within capture sessions (range 7.6 - 19.6 m) and between range capture sessions (range 8.9 - 32.6 m). 5. The results of this study are consistent with expectations if removal by trapping lowered population densities, which we speculate may have affected movement distances directly, or indirectly through increasing the availability of food and shelter. 5. The results of this study are consistent with expectations if removal by trapping lowered population densities, which we speculate may have affected movement distances directly, or indirectly through increasing the availability of food and shelter.